(untitled) (Journal of Hama University, 2022)
Given the importance of the role of health institutions in providing health care services to a wide segment of society, and the importance of administrative empowerment related to the quality and efficiency of these institutions, and because that the lack of minimum administrative empowerment among the nursing staff may have negative repercussions on the level of health care quality,The aim of the study: to assess the level of administrative empowerment of the nursing staff at Al-Assad Medical Hospital in the city of Hama, A descriptive cross-sectional study was conducted on an appropriate sample of 301 nursing staff at Al-Assad Medical Hospital in Hama, and the data were collected using a pre-designed questionnaire for this purpose.The results of the current study showed that most of the nursing staff had a moderate level of total administrative empowerment, and they also had a moderate level of administrative empowerment in all its aspects, except for the work teams axis, which was high. The axis of work teams ranked first among the administrative empowerment axes, followed by the axis of effective communication, then the axis of delegation of authority, the axis of training, and finally the axis of motivation. his study recommended working to increase the interest of the senior administrative leaders in the hospital to achieve more administrative empowerment for the members of the nursing staff, and to pay attention to developing the administrative capabilities of the nursing staff, and to conduct similar studies that include a wide range of nursing bodies.